2016
DOI: 10.1128/jvi.02030-15
|View full text |Cite
|
Sign up to set email alerts
|

Pan-genotypic Hepatitis C Virus Inhibition by Natural Products Derived from the Wild Egyptian Artichoke

Abstract: Hepatitis C virus (HCV) infection is the leading cause of chronic liver diseases. Water extracts of the leaves of the wild Egyptian artichoke (WEA) [Cynara cardunculus L. var. sylvestris (Lam.) Fiori] have been used for centuries in the Sinai Peninsula to treat hepatitis symptoms. Here we isolated and characterized six compounds from the water extracts of WEA and evaluated their HCV inhibition capacities in vitro. Importantly, two of these compounds, grosheimol and cynaropicrin, inhibited HCV with half-maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…21 The anti-HCV activity of WEA was thus verified in the current clinical trial and in our previously reported in vitro studies. In Huber's study, it was reported that the artichoke extract of "Hepar SL forte ® " showed neither activity as anti-HCV, nor cholesterol and ALT lowering effects.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…21 The anti-HCV activity of WEA was thus verified in the current clinical trial and in our previously reported in vitro studies. In Huber's study, it was reported that the artichoke extract of "Hepar SL forte ® " showed neither activity as anti-HCV, nor cholesterol and ALT lowering effects.…”
Section: Resultssupporting
confidence: 76%
“…10 Apart from their nutritive value, artichoke extracts are well reported to exhibit antitumor, anti-hyperlipidemic, choleretic, anti-oxidant, hepatoprotective, and anti-inflammatory activities. 21 Cynaropicrin is the major bitter compound present in artichoke and its highest concentration found in leaves (especially in trichomes), and is almost absent in roots, stems and in completely developed inflorescences. 11 Huber et al 15 reported that the artichoke extract of "Hepar SL forte ® " showed no cholesterol lowering effects, although the cholesterol-lowering and hepatoprotective activities of artichoke were well verified by several other groups.…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether lipoquads can inhibit HCV cell-to-cell transmission, we used an agarose overlay-based assay which inhibits cell-free virus, using a previously described infection reporter system (35). In this infection reporter system, Jc1 HCVcc-infected Huh7/Scr cells act as virus donor cells and uninfected Huh7.5/EGFP-NLS-IPS as acceptor cells (35,36). The latter cells stably express a chimeric enhanced green fluorescent protein (EGFP) which upon HCV infection is redistributed from mitochondria to the nucleus (a complete description of these cells is available in Materials and Methods).…”
Section: Figmentioning
confidence: 99%
“…Cynaropicrin, a sesquiterpene lactone (STL), is a major biologically signi cant class of secondary metabolites in the artichoke (14). Cynaropicrin has been shown to possess various pharmacologic properties, such as anti-hepatitis C virus (15), anti-parasitic (16), anti-photo aging (17), anti-in ammatory (18), and anti-tumor properties. In human leukemia and prostate cancer cells, cynaropicrin is able to induce glutathione depletion and result in S-glutathionylation of STAT3, leading to down-regulation of STAT3-dependent gene expression and chemosensitization of tumor cells to chemotherapy (19).…”
Section: Introductionmentioning
confidence: 99%